Compost Fertilizer from Municipal Solid Wastes and its Application in Urban Agro-forestry Nurseries: A Case Study on Khulna City - Tusar Kanti Roy,; Saima Rahman,; Papon Kumar Dev, (Journal of Bangladesh Institute of Planners, 2013)
About 70% of the total produced 520 tons of municipal solid wastes per day in Khulna city is organic and suitable for preparation of compost fertilizer. Among the NGOs involved in solid waste management only RUSTIC at present is producing about 30 tons compost per month on its own plant of 0.47 acre land using only 46 tons (0.53%) from 8730 tons. Additional 5663 tons of compost per month can be produced from the unused 8684 tons (99.47%) of organic wastes. In spite of having huge demand for organic compost, only 33% agro-forestry nurseries in Khulna city and its adjoining areas are using the compost fertilizer claiming its low quality and due to having lack of awareness. The compost can be used to the city nurseries for increasing their productivity, reducing the volume of waste to be disposed of and thereby to create healthier urban environment of Khulna city. Journal of Bangladesh Institute of Planners, Vol. 6, Dec 2013, pp. 191-199